Hybrid Restorative Justice: Optimizing Cessation Of Prosecution The Case Theft Through Restorative Judicial House - Daffa Ladro Kusworo; Maghfira Nur Khaliza Fauzi (Faculty of Law, Universitas Lampung, 2022)
The existence of restorative justice certainly brings a new paradigm in settlement of criminal cases, with the settlement of cases solely out of court. Restorative justice-based law enforcement is manifested in all law enforcement agencies, especially the Prosecutor's Office, in prosecuting cases based on the Republic of Indonesia Prosecutor's Regulation Number 15 of the Year 2020 concerning the Termination of Prosecution Based on Restorative Justice. The amount required to prosecute restoratives can be applied to the crime of theft as the highest case in Indonesia. This happened because Indonesia's disrupted economy after the Covid-19 pandemic created a moral crisis with drastic theft crimes. Meanwhile, it was recently discovered that establishing a restorative justice house in each jurisdiction of the attorney general's office was found to optimize the resolution of all legal problems by screening cases that go to court, socializing the law to residents, and being able to develop local wisdom. Involving local traditional leaders to emphasize deliberation is also another important thing wich must be exereised. This research uses normative legal research methods through applicable laws and regulations and literature study. The legislative approach is sourced from primary data and literature studies. Then in analyzing the problem, the author uses a descriptive analysis approach by applying the deductive method, namely, concluding a general discussion into a specific statement. Of course, the restorative justice house guarantees legal certainty and is an adequate facility in its implementation. Moreover, the Attorney General's Office has also formed a Quick Response Task Force to maximize the role of the restorative justice house by providing input on cases that deserve to be resolved through restorative justice, one of which is the crime of theft, which is happening.